BOOK REVIEW OFONE DAY WRITTEN BY DAVID NICHOLLS - DHEA, ISTYANI (LANTERN (Journal on English Language, Culture and Literature), 2015)
This book review analyzes the strengths and weakness of David Nicholls’s One Day. One Day is a novel that tells the story about a man and woman who actually loves each other, but they never shows it up for about 20years because of their prestige feeling. This review explores the strengths and the weakness of David Nicholls’s One Day by inspecting elements namely characters, setting, and conflict. To review the novel, the writer use intrinsic theory such as characters, settings, and conflict. In addition, the writer use close reading method to analyze this novel. I choose this novel, because this novel has strengths that make it as a good reading. The strengths inside the novel are characters and conflict. In this novel each character has a different characteristic and is highly contrasted, it makes the story more exciting and not boring. On the other hand, the conflict is so strong in this novel. The way Nicholls explains the conflict could make the reader feels what exactly the character’s feel. Even having weakness, this novel is not less the value to be a good reading. One Day is recommended novel to read, because there are many interesting parts of the story that we can enjoy from this novel. Keyword: characters, setting, conflict, strengths, and weakness.